An Evaluative Study of the Experiential Learning of Immersion Students Through the Convergent Parallel Approach - Mercado, Matias; Calvez, Keen Jolliheart; Mercado, Cornelio; Jovero, Neilgene; Acuram, Miral (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the success of the work immersion program among Grade 12 students at Holy Cross of Mintal, Inc., focusing on experiential learning as a determinant of program effectiveness. Anchored on Kolb’s Experiential Learning Theory, the study employed a convergent parallel mixed-methods design integrating quantitative and qualitative approaches. Data were collected from all eligible students using a 23-item Likert-scale questionnaire and from 15 selected participants through open-ended questions and unstructured interviews. Quantitative data were analyzed using descriptive statistics, correlation, and regression, while qualitative data were examined through thematic analysis. Findings revealed a high level of experiential learning, with concrete experience rated very high and other dimensions rated high. The work immersion program was generally perceived as successful, particularly in pre-deployment activities and adviser monitoring, although inconsistencies were observed in partner institution cooperation. A strong and significant relationship between experiential learning and program success was identified, with reflective, applying, and concluding experiences emerging as key predictors, explaining a substantial portion of program success. Qualitative results supported these findings, highlighting students’ development of responsibility, professional identity, and workplace adaptability, while also identifying gaps in pre-deployment readiness and industry coordination. The study concludes that the effectiveness of work immersion depends on deeper cognitive engagement, particularly reflection and application, rather than mere exposure. It recommends strengthening reflective practices, improving industry collaboration, and enhancing pre-deployment preparation. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 17 (Partnerships for the Goals) by promoting effective experiential learning and school-industry collaboration. It contributes to educational, institutional, and socio-economic sustainability by improving curriculum implementation, workforce readiness, and alignment between academic training and industry demands.